Strategies to Decrease the Prevalence of Soil-Transmitted Helminths in Central India - Sharma, Archa; Purwar, Shashank; Gupta, Shipra; Gupta, Ayush; Gautam, Disha (Journal of Laboratory Physicians, 2022)
Background Intestinal parasites are a major public health problem in tropical countries. Over 1.5 billion people are infected with soil-transmitted helminths (STH), of which 225 million are in India. Parasitic infections are associated with poor sanitation, lack of safe potable water, and improper hygiene.Materials and Methods The study was undertaken to ascertain the impact of control strategies, namely open-defecation free drive and mass drug administration of single dose albendazole. Stool samples received at AIIMS Bhopal Microbiology laboratory, across all age groups, were studied for protozoan trophozoites/cysts and helminthic ova.Results Out of 4,620 stool samples, 389 (8.41%) were positive either for protozoal or helminthic infections. Protozoan infections were more common than helminthic infections with Giardia duodenalis infection being the most common, 201 (51.67%), followed by Entamoeba histolytica, 174 (44.73%). The helminthic infections constituted 14 (3.5%) of the positive stool samples with Hookworm ova in 6 (1.5%) cases.Conclusion This study proves that strategies, namely “Swachh Bharat Abhiyan” and “National Deworming Day” started in 2014 and 2015 led to significant reduction of intestinal parasite infections in Central India, with a higher reduction of STH compared with protozoan parasite infection being ascribed to the activity spectrum of albendazole.
Keywords: soil-transmitted helminths; neglected tropical disease; central India; National Deworming Day; Swachh Bharat Abhiyan